The validity of immunohistochemistry in detecting microsatellite instability in pediatric solid neoplasms - Khaldoon Aljerian; Waleed AlRajban; Tariq Aljohani; Ali Alshehri; Omar Alsherif; Musa Alharbi; Ibraheem Abosoudah; Wasil Jastaniah; Saad Al Daama; Abdulrahman AlSultan; Nahaa Eid Alsubaie (Wolters Kluwer Medknow Publications, 2024)
Background: The DNA mismatch repair (MMR) is the biological pathway that plays a key role in maintaining genomic stability during DNA replication and recombination. The value of MMR pathway is under investigation in pediatrics' solid tumors. Aims: In this research work, we investigated the proteins involved in the oncogenesis of pediatric solid neoplasms and detect these proteins in a representative cohort sample of Saudi pediatric cases under the bioinformatic networking technique. We also described the MLH1, BRAF, p53, proliferating cell nuclear antigen, and PMS2 along with MSH2-MSH6 antibodies to be a diagnostic immunohistochemistry (IHC) panel for identifying MMR mutations. This research will open the new doors for advanced research on proteins involved in the oncogenesis of pediatric solid neoplasms. The hypotheses were tested on a sample of solid malignancies and IHC results were reported. Material and Methods: The study was conducted in different institutions in Saudi Arabia. The inclusion criteria required enrolling biopsies of solid neoplasms or resected solid malignant neoplasms presented to the laboratories in the participating institutions of all pediatric patients (aging from 0 to 14 years). The specimens were examined microscopically utilizing Hematoxylin and Eosin stain as well as the utilization of MMR proteins immunohistochemistry (IHC), and PNCA. Results: The qualitative assessment showed that IHC diagnosis yielded positive results with ≥80% of positive cells (intact) for MMR proteins (MSH2, MSH6, PMS2, and MLH1). The PCNA protein was absent only in vaginal germ cell tumor and metastatic medulloblastoma. Conclusion: In our sample, we have found that there is an intact MMR proteins expression. Also, the IHC technique presents accuracy and ability as a diagnostic technique for identifying the different types of pediatric cancers. The MMR protein panel accompanied with PCNA panels holds additional value, as it helps reduce dependency solely on MMR protein expressions.